Law on Sexual Violence Crime (TPKS): Abolishing Restorative Justice and Prioritising Victims’ Rights - Riyanto, Pandu Irawan; Barung, Anselmus A.Y. (Departemen Sosiologi Universitas Gadjah Mada, 2025)
In Indonesia, the resolution of sexual violence cases often involves out-of-court mechanisms or restorative justice settlements. Following the enactment of the Law on Sexual Violence Crime (hereinafter abbreviated as TPKS), there should be no further out-of-court law settlements as explicitly regulated in Article 23. This paper seeks to criticise the prevailing practice of restorative justice. In addition, this article discusses the TPKS Law as a legal framework that favours the rights of victims using a feminist standpoint approach. The research method in this study is descriptive qualitative, using various sources of literature as its data sources. The results show that the implementation of restorative justice has ignored the aspects of unequal power relations between victims and perpetrators, which resulted in re-victimisation and the neglect of victims' rights. The TPKS Law is a starting point for the abolition of restorative justice practices in resolving sexual violence cases. The TPKS Law guarantees more protection for victims' rights, making victims more empowered and avoiding intimidating treatment from law enforcement officials and perpetrators. However, the TPKS Law has not been integrated with regulations in law enforcement institutions. Thus, guidelines for handling sexual violence based on the TPKS Law are essential for law enforcement institutions, ensuring a more gender-sensitive approach while permanently halting the practice of restorative justice in such cases.